STEM Education in Enhancing Creative Thinking and Attitudes Towards Science of Grade 7 Students - Boasupee, Jintana; Dokmai, Panwilai (Interdisciplinary Academic and Research Journal, 2023)
The 21st century is an era of innovation and technology that has developed exponentially. Students must therefore be developed to achieve learning. Understand and be able to apply knowledge creatively Therefore, the purposes of this study were 1) to compare the creative thinking of grade 7 students between pre-test and post-test scores of STEM education on Thermal Energy, 2) to compare the learning achievement of grade 7 students between pre-test and post-test scores of STEM education on Thermal Energy and 3) to study attitudes towards sciences after the STEM education on Thermal energy. The sample group was 42 grade 7 students at Anukoolnaree School from cluster random sampling technique. The research instruments were 1) STEM lesson plans on thermal energy for 21 hours, 2) creative thinking, 3) learning achievement tests, and 4) attitudes towards sciences inventory. The data analysis statistics were mean, standard deviation, and Dependent-Samples t-test. The research revealed that 1) grade 7 students had creative thinking post-test average scores higher than the pre-test average score with a statistically significant difference at level 5, and 2) grade 7 students had learning achievement post-test average scores higher than the pre-test average score.